A Comparative Study on the Proximate Composition and Protein Quality of Soya Bean Flour and Smoked Crayfish Sold in Dschang, Cameroon (Global Journal of Science Frontier Research, 2022)
A study was carried out to compare the proximate composition and protein quality of soya beans flour and smoked crayfish. Proximate compositions of soya beans flour and smoked crayfish were determined and diets composed for rat growth and balance experimentation. Eighteen (18) weanling male wistar rats were distributed in three groups of six elements. Test groups received respectively soya beans-based and smoked crayfish-based diets. Each protein product was fed as the sole source of 10% dietary protein. The evaluated biological parameters were protein efficiency ratio (PER) and net protein ratio (NPR). Smoked crayfish had significantly (p
Keywords: proximate composition; soya bean flour; smoked crayfish; protein quality; PER; NPR